The Validation of an Innovative Method for 3D Capture and Analysis of the Nasolabial Region in Cleft Cases. (January 2021) - Ayoub, Ashraf; Khan, Adil; Aldhanhani, Ali; Alnaser, Hashim; Naudi, Kurt; Ju, Xiangyang; Gillgrass, Toby; Mossey, Peter
Objective: To validate a newly developed method for capturing 3-dimensional (3D) images of the nasolabial region for assessing upper lip scarring and asymmetry in surgically managed unilateral cleft lip and palate (UCLP) cases. Design: Validation study, single cohort. Materials and Methods: Eighteen surgically managed UCLP cases were recruited, the nasolabial region of each face was scanned using an intraoral scanner (IOS) to produce 3D images. The images were manually segmented to allow the calculation of surface area of the scar and upper lip asymmetry. Five professionals and 5 lay assessors subjectively evaluated the same images and graded the upper lip scarring and asymmetry at 2 separate occasions. The relationship between the subjective and objective assessments was evaluated. Results: Moderate correlation was found between subjective and objective evaluations of the upper lip scarring and total asymmetry. The captured 3D images were of good quality for the objective measurements of lip asymmetry and residual scarring. Moderate to strong correlations were detected between the 2 panels (T ranging between 0.5 and 0.9) with no significant difference ( P > .05) in the mean score of the subjectively evaluated parameters. Conclusion: The IOS is a useful tool for the capture of the nasolabial morphology. The captured 3D images are a reliable source for measuring lip asymmetry and scar surface area. The method has sufficient validity for routine clinical use and for objective outcome measures of the surgical repair of cleft lip.